O processo legislativo e a necessidade - Passos, Edilenice (Revista General de Información y Documentación, 2002)
This article describes the Brazilian legislative process and identifies the role of the Consultoria Legislativa together with its information needs and the main sources used to satisfy these needs.
Keywords: Legislative Process; Brazil; Consultancy Staff; Federal Senate; Information sources